TAX AGGRESIVENESS, BOARD DIVERSITY DAN UKURAN PERUSAHAAN TERHADAP KUALITAS LABA - Hastuti, Eka Sri; Romadhina, Anggun Putri (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
This research aims to determine the effect of Tax Aggressiveness, Board Diversity and company size on earnings quality. This research uses a sample of Non-Cyclical Consumer Sector Companies on the Indonesia Stock Exchange 2019-2023. The data used in this research are financial reports and annual reports. This research sample was determined using a purposive sampling method and based on criteria obtained from 14 company data and analyzed using panel data regression techniques with a fixed effect model to test the hypothesis. The data was processed with the help of Eviews 13 software. The results obtained show that tax aggressiveness, board diversity and company size simultaneously influence earnings quality. The results obtained partially show that tax aggressiveness has no effect on earnings quality, board diversity has no effect on earnings quality and company size has an effect on earnings quality.